Faculty Liaisons: an embedded approach for enriching teaching and learning in higher education. Issue 3 (3rd July 2019) - Sharif, Afsaneh; Welsh, Ashley; Myers, Jason; Wilson, Brian; Chan, Judy; Cho, Sunah; Miller, Jeff
ABSTRACT: This paper explores the experiences of a group of academic developers who support educational development work as Faculty Liaisons at a large, research-intensive university. These academic developers inhabit complex 'third spaces', providing support through an embedded partnership relationship that requires lateral movement across functional and organizational boundaries to create new professional spaces, knowledge, and relationships. The authors utilize narrative inquiry and auto-ethnographic approaches to present an interpretive qualitative analysis of their experiences supporting Faculty and University projects across complex and evolving organizational boundaries. From this analysis, they highlight key roles and responsibilities associated with their blended context and identify challenges that academic developers who occupy third spaces within academic organizations face as they negotiate competing interests, identities, and requirements associated with the diverse range of their projects and the blended experience of working in scholarly and administrative, central- and Faculty-based roles. The lessons they have learned from these experiences will be of particular interest to academic developers who are experiencing the flux of change within higher education settings that are impacting teaching and learning practices both for faculty in the classroom and for those across the institution who support them.